Unveiling successes and pitfalls: navigating human resource development in komunitas kejar mimpi pontianak - Jaya, Arman; Saputra, Dimas (Institute of Computer Science (IOCS), 2024)
This study aimed to identify best practices and areas for improvement in enhancing the quality of Human Resources within Komunitas Kejar Mimpi Pontianak. Employing a qualitative approach, the research conducted a case study within the organization. Data collection methods included in-depth interviews, observation, documentation review, and focus group discussions. Data analysis utilized the interactive analysis technique proposed by Miles & Huberman. Findings revealed several best practices contributing to Human Resource development in Komunitas Kejar Mimpi Pontianak, such as member appreciation, active member involvement, targeted short-term training programs, adaptability to dynamic changes, and fostering strong member bonds. Conversely, areas requiring improvement, or